Diagnostic Value of Metagenomic Next-Generation Sequencing for Pulmonary Infection in Intensive Care Unit and Non-Intensive Care Unit Patients - Zhou, Jing-Jiang; Ding, Wei-Chao; Liu, Yan-Cun; Gao, Yu-Lei; Xu, Lei; Geng, Run-Lu; Ye, Ying; Chai, Yan-Fen (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To evaluate the diagnostic performance of metagenomic next-generation sequencing (mNGS) and culture in pathogen detection among ICU and non-ICU patients with suspected pulmonary infection. Methods: In this prospective study, sputum samples were collected from patients with suspected pulmonary infection for 2 consecutive days, and then subjected to DNA or RNA sequencing by mNGS, or culture, 62 ICU patients and 60 non-ICU patients were admitted in. At the end, comparisons were made on the pathogen species identified by mNGS and culture, the overall performance of these two methods in pathogen detection, as well as the most common pathogens detected by mNGS between the ICU and non-ICU groups. Results: In DNA and RNA sequencing, the positive rate of pathogen detection reached 96.69% (117/121) and 96.43% (108/112). In culture tests, the positive rate of pathogen was 39.34% (48/122), much lower than those of DNA and RNA sequencing. In general, the positive rate of pathogen detection by sputum mNGS was significantly higher than that of sputum culture in the Total and non-ICU groups (P < 0.001), but did not show significant difference when compared to the result of sputum culture in the ICU group (P = 0.08), Haemophilus spp., Candida albicans, Enterococcus spp. and viruses from the mNGS results were excluded before comparing the overall performance of these two methods in pathogen detection. Specifically, among the 10 most common bacteria implied from the mNGS results, significant differences were observed in the number of cases of Haemophilus parainfluenzae, Acinetobacter baumannii, Klebsiella pneumoniae, Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Staphylococcus aureus and Enterococcus faecalis between the ICU and non-ICU groups (P < 0.05). Conclusions: This study demonstrated the superiority of mNGS over culture in detecting all kinds of pathogen species in sputum samples. These results indicate that mNGS may serve as a valuable tool to identify pathogens, especially for ICU patients who are more susceptible to mixed infections.